2008
DOI: 10.1002/jae.1031
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐round procurement auctions with secret reserve prices: theory and evidence

Abstract: When a secret reserve price is used in an auction, the auctioneer cannot guarantee that the good can be sold out at the auction, and can re-auction the unsold objects in the next round.Motivated by this interesting feature observed in the procurement auctions organized by the Indiana Department of Transportation, we construct a bidding model in multi-round procurement auctions with secret reserve prices and evaluate how the release of the auctioneer's reserve price a¤ects bidders'bidding behavior and the aucti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, many types of goods are auctioned subject to secret reserves, including oil and gas leases, timberland, construction contracts, and wine—in addition to fine art. Empirical studies of auctions with secret reserves, for example Elyakime et al (1997) and Ji and Li (2008), have so far been limited to situations where the reserve price is ultimately revealed—before the model is empirically estimated. Our research extends the econometric analysis of auctions into the realm of an unknown and unobservable reserve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many types of goods are auctioned subject to secret reserves, including oil and gas leases, timberland, construction contracts, and wine—in addition to fine art. Empirical studies of auctions with secret reserves, for example Elyakime et al (1997) and Ji and Li (2008), have so far been limited to situations where the reserve price is ultimately revealed—before the model is empirically estimated. Our research extends the econometric analysis of auctions into the realm of an unknown and unobservable reserve.…”
Section: Introductionmentioning
confidence: 99%
“… Ji and Li (2008), in contrast, assume that the distribution of the unknown reserve is exponential.…”
mentioning
confidence: 99%
“…They concluded that the first effect explained above dominates the second effect, thus leading to an increase in firms' costs. Ji and Li (2008a) exploited a multi-round feature of procurement auctions conducted by the Indiana Department of Transportation. Specifically, if a contract is not awarded (perhaps because all bids exceed a price ceiling in a low-price setting) the government may re-auction the contract in additional rounds.…”
Section: Auction Dynamicsmentioning
confidence: 99%
“…Elyakime, Laffont, Loisel, and Vuong (1994) and Eklöf and Lunander (2003) argue that while public reserve prices may be optimal, secret reserve prices yield higher sales, which benefits the auctioneer when paid a percentage of sales. Ji and Li (2008) study multiround auctions with a secret reserve price and find via numerical simulations that a secret reserve price can yield lower expected procurement costs than a public reserve price, when the mean of bidders' cost distribution exceeds the mean reserve price.…”
Section: Introductionmentioning
confidence: 99%